A dinâmica das relações familiares por adultos que cresceram em famílias de pais separados na infância - Wajss, Caroline (2022)
This work had as main objective to discuss the dynamics of family relationships by adults who had their parents separated in childhood. The new family structures are part of today's society, and the focus of this study prioritized the first generation of adults after the 1977 divorce law. In addition to parental relationships, such as stepmothers, stepfathers, siblings, half-siblings or cosiblings were also learned. The main theoretical assumptions were based on the foundations of systemic therapy, which encompasses the epistemology of new-paradigmatic science, making it possible to understand the new contemporary family arrangements in their complexity, instability and subjectivity. To achieve this objective, eleven semi-structured interviews and the genogram of each participant were carried out. Through the qualitative analysis of the data, from the narratives of the interviewees, categories were raised that pointed out some questions relevant to the research objective. The results obtained show the diversity of these relationships, point to the complexity of dealing with new family members over time, the conflicts generated in moving through different houses and the perception of children in the relationship with their parents in adult life